A Comparison Between Two Public Expenditure Management Systems in Africa - Lienert, Ian (OECD Publishing, 2003)
Many African countries are benefiting from reductions in their external debt. One important objective is to redirect the budgetary resources released from servicing external debt towards poverty-reducing expenditures. Several questions arise in this context. First, are the public expenditure management (PEM) systems of African countries robust enough to allow specific povertyreducingexpenditures to be identified in annual budgets and tracked in countries' accounting systems? Second, does the expenditure control system allow poverty-reducing expenditures to be protected from cuts should there be unforeseen shortfalls in revenues? Third, are internal and external audit mechanisms effective, so as to ensure the integrity of expenditure reports, both in-year and annually? To answer these and other questions, an assessment of the entire PEM system is required in each country. Such a study has already been prepared.1 During 2001, the PEM systems of 24 low-income countries were assessed based on a common set of 15 questions in the areas of budget preparation, budget execution, and fiscal reporting. Figure 1 shows the results for two regions of Africa (Anglophone countries and Francophone countries) - well below what is required to meet the objectives of effective PEM systems (both regions attained only about 40% of the required benchmarks)...
Keywords: Governance